Efficacy and safety of lyophilized concentrate purple corn (Zea mays L.) in preventing the formation of colonic polyps - Ichiyanagui R., Carlos (2021)
Introduction: Colorectal cancer (CRC) is a worldwide problem of public health and arises mainly from polyps. In last 25 years, a strategy called chemoprevention that consists of food intake like purple corn and turmeric or chemical substances like acetyl salicylic acid (ASA) and non-steroidal anti-inflammatory drugs (NSAIDs) that prevent effectively carcinogenesis reducing the risk of polyp development. Objective: To determine the efficacy and safety of lyophilized concentrate of purple corn (Zea mays L.) 200 mg in the prevention of colonic polyps development in private gastroenterological practice Methods: we randomly assigned 112 patients (cases) to receive this product and 112 patients (controls) to receive placebo, during 3 years. Both groups had similar demographic, clinical and medical history characteristics. Results: we found that cases developed 83% less polyps than controls (p<0.001). The cases that developed polyps were smaller in number, size and histology than at the beginning of the trial. The adverse events that cases presented were 4.5% similar to controls, mainly petechiae. Conclusion: We conclude that the lyophilize 0 mg was effective and safe in preventing the development of colonic polyps.